Vacuum Evaporator Design Liquid Ring Vacuum Pump Method - Siswanto; Nurul Widji Triana (Nusantara Science and Technology Proceedings)
The evaporation process in the nira with vacuum evaporator using barometric condenser requires considerable energy, to save energy, it is necessary to design a vacuum evaporator that can decrease the point also energy-saving by replacing the barometric condenser into Liquid Ring Vacuum Pump method where the vapor has been condensed in the condenser is flown to the vacuum pump to draw steam in the evaporator chamber so that vacuum conditions occur. This type of vacuum pump uses a small energy when compared with using a steam jet ejector and is expected to use the vacuum evaporator with the Liquid Ring Vacuum Pump Method will be able to save electrical power. Vacuum Pump vacuum design with Liquid Ring Vacuum Pump method can reduce the evaporation temperature to 76 °C with a level of vacuum reaching 200 mm Hg against pressure 760 mm Hg. The results of vacuum evaporator design is expected to be used in industries that use the evaporation process of a solution that is sensitive to high temperatures, by making the vacuum condition will decrease the boiling point which will automatically save costs in the evaporation process.